2022
DOI: 10.4266/acc.2022.00136
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with development of coinfection in critically Ill patients with COVID-19

Abstract: Background: At outset of the coronavirus disease 2019 (COVID-19) pandemic, the significance of bacterial and fungal coinfections in individuals with COVID-19 was unknown. Initial reports indicated that the prevalence of coinfection in the general population was low, but there was uncertainty regarding the risk of coinfection in critically ill patients.Methods: Nine hundred critically ill adult patients with COVID-19 infection were enrolled in this observational case-control study. Patients with a coinfection (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…Secondly, a significant factor is the possibility of nosocomial coinfections in critically ill patients during COVID-19 related which results in prolonged hospitalization. [21] To preclude this situation, targeted plans to improve the long-term infection control measures within the relevant facilities are essential. Another finding that may require scientific interpretation is that the high prevalence of males (77.7%) in recruited patients compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, a significant factor is the possibility of nosocomial coinfections in critically ill patients during COVID-19 related which results in prolonged hospitalization. [21] To preclude this situation, targeted plans to improve the long-term infection control measures within the relevant facilities are essential. Another finding that may require scientific interpretation is that the high prevalence of males (77.7%) in recruited patients compared to females.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 Hospital-acquired superinfections were reported more than co-infections in multiple other articles. 9 , 12 , 14 , 15 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with multiple studies, which showed that the length of hospital stay increased exponentially both locally (16.2 vs. 35.2 days), and internationally where the duration of ICU stay was 6.7 vs. 13.8 days, and hospital stay was 11.8 vs. 18.6 days. 9 , 17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations